THE SPECIFICITY OF RELIGIOUS DISCOURSE: A COMPARATIVE AND INTERDISCIPLINARY PERSPECTIVE - Toshpulatova Mukhlisa (Innovate Conferences, 2025)
This article explores the specificity of religious discourse as a distinct mode of communication that shapes and reflects belief, identity, and tradition. It examines the values and precedents embedded in religious discourse, highlighting how ideals such as faith, goodness, and grace are formed, transmitted, and practiced in daily life. Special attention is given to the precedent phenomenon, where past figures and events, such as the lives of the Prophet Muhammad (PBUH) in Islam or Jesus Christ in Christianity, serve as enduring models for contemporary believers. The study employs a comparative approach, analyzing Islamic and Christian discourses with respect to their sources, structures, and unique characteristics, ranging from the textual centrality of the Qur’an and Hadith to the Christocentric and grace-oriented nature of Christian discourse. Interdisciplinary perspectives from sociolinguistics, discourse analysis, and cognitive linguistics are drawn upon to frame the study, while challenges of diversity, complexity, interpretation, and researcher objectivity are critically considered. Ultimately, the paper underscores the need for openness, methodological rigor, and transparency when engaging with religious discourse, situating it as both a field of scholarly inquiry and a lived practice with enduring cultural and spiritual significance.
Keywords: religious discourse; values and precedents; Islam; Christianity; comparative study; sociolinguistics; discourse analysis; cognitive linguistics; faith and grace; objectivity in research.